The Effect Of Blood Type On The Incidence Of Diabetes Mellitus In The Elderly - Sari, Diah Jerita Eka; Mindiharto, S.PSi., M.Kes, sestiono (Journal of Public Health Science Research (JPHSR), 2020)
The increasing population of the elderly in the community cannot be separated from the health problems they experience. Various problems related to the decline in physical condition in the elderly will lead to various degenerative diseases . F. Degenerati disease f in elderly if not handled properly will decrease the quality of their lives so that it can increase morbidity and mortality. Various diseases degenerati f the most widely experienced by the elderly, among others, joint disorders, hypertension, mental and emotional disorders, heart disease, cataracts, stroke, and diabetes mellitus. Diabetes afflicts many Indonesians. Every year it gets bigger in number, and this can be disastrous. Diabetes is a very dangerous disease. If not treated properly, it will cause various complications that can make people suffer and can even cause death. Complications can include nerve damage, impaired blood circulation, kidney problems, heart problems, high blood pressure, and so on. The number of diabetics in Southeast Asia is Singapore 12.8%, Thailand 8%, Malaysia 16.6%, and in Indonesia 6.2% (IDF 2015). If in 2015 it is at number seven as a country with the highest number of diabetes patients in the world, in 2040 it is estimated that Indonesia will rise to number six. Blood type is a key to the entire immune system, and an essential explanatory factor in a person's health profile. Blood group antigen creates antibodies. Several studies on blood groups have shown that certain blood groups have a risk of certain problems or diseases related to the interaction of miscroscopic substances on the surface of red blood cells interacting with the immune system . Blood type cannot be changed, but knowing the effect of blood group on the incidence of diabetes mellitus allows for proper preventive action